2020
DOI: 10.3389/fmicb.2019.02993
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal Cell Wall: Candida, Cryptococcus, and Aspergillus Species

Abstract: The fungal cell wall is located outside the plasma membrane and is the cell compartment that mediates all the relationships of the cell with the environment. It protects the contents of the cell, gives rigidity and defines the cellular structure. The cell wall is a skeleton with high plasticity that protects the cell from different stresses, among which osmotic changes stand out. The cell wall allows interaction with the external environment since some of its proteins are adhesins and receptors. Since, some co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
410
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 574 publications
(423 citation statements)
references
References 161 publications
(216 reference statements)
7
410
1
5
Order By: Relevance
“…The outer layer of the C. albicans cell wall is said to be packed with mannoproteins and cross-linked to β-1,6-glucans and, unlike Aspergillus spp., α-glucan is absent from Candida spp. cell walls [31]. C. albicans has also been hypothesized to initiate its own uptake by host cells via complement proteins or complement receptors as an alternative immune evasion strategy [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer layer of the C. albicans cell wall is said to be packed with mannoproteins and cross-linked to β-1,6-glucans and, unlike Aspergillus spp., α-glucan is absent from Candida spp. cell walls [31]. C. albicans has also been hypothesized to initiate its own uptake by host cells via complement proteins or complement receptors as an alternative immune evasion strategy [32].…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans has also been hypothesized to initiate its own uptake by host cells via complement proteins or complement receptors as an alternative immune evasion strategy [32]. It has also been reported that these mannoproteins are glycosylphosphatidylinositol-modified during interactions with the host, allowing the activation of the immune response by masking the β-glucan layer and thereby leading to an ineffective activation of the host immune system [31]. Similarly, it has been reported that C. albicans tended to cause higher inflammatory cytokine and chemokine concentrations, along with increased neutrophils and inflammatory monocytes, compared with nonalbicans Candida infections [33].…”
Section: Discussionmentioning
confidence: 99%
“…This subsequently alters the passage of nutrients through the cell wall into the periplasmic space and to the plasma membrane. As such, the fungal cell wall represents an ideal target for antifungals [158,[167][168][169]. -glucan with notable differences in their architecture and attachments to these basal components.…”
Section: The Cell Wall Composition Of Mucorales In Comparison To Othementioning
confidence: 99%
“…For example, the cell wall of C. albicans contains β-(1,6-) linkages, while Aspergillus spp. do not [165,168,173,174]. The most important component of the cell wall is the β-1,3-D-glucan, which is synthesised by 1,3-β-D-glucan synthase.…”
Section: The Cell Wall Composition Of Mucorales In Comparison To Othementioning
confidence: 99%
See 1 more Smart Citation